ICOS ATC CO Release from Hyltemossa (150.0 m), 2017-04-17–2026-03-31 - Michal Heliasz; Tobias Biermann (Integrated Carbon Observation System, 2026)
Quality-controlled data on molar fraction of atmospheric CO
Heliasz, M., Biermann, T. (2026). ICOS ATC CO Release from Hyltemossa (150.0 m), 2017-04-17–2026-03-31, ICOS RI, https://hdl.handle.net/11676/u7YfJMiga0WcN_msY3b7pktc
Keywords: Atmosphere Thematic Centre; CO; ICOS; dry air mole fraction; time instant, UTC; time instant, UTC; quality flag; quality flag; number of points; number of points; standard deviation of gas mole fraction; standard deviation of gas mole fraction; CO (dry air mole fraction); CO (dry air mole fraction); Oceanography, Hydrology and Water Resources; Oceanografi, hydrologi och vattenresurser; Meteorology and Atmospheric Sciences; Meteorologi och atmosfärsvetenskap; Physical Geography; Naturgeografi; Environmental Sciences; Miljövetenskap; Climate Science; Klimatvetenskap